2022
DOI: 10.52547/rbmb.10.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of circRNA-HIPK3/microRNA-124a Crosstalk in the Pathogenesis of Rheumatoid Arthritis

Abstract: Background: Circular RNA-HIPK3 (CircHIPK3) has been shown to be aberrantly expressed in a variety of diseases, contributing to disease initiation and progression. The aim of the present study is to investigate the role of the circHIPK3 RNA/microRNA-124a interaction in the pathogenesis of rheumatoid arthritis (RA). Methods: This study included 79 RA patients and 30 control individuals. The patients involved were classified according to the disease activity score (DAS28) into mild (24 patients), moderate (24 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Notably, a co-expression relationship exists between circRNAs and miRNAs. After its transcription, circRNAs cooperate with miRNAs to participate in the regulation of RA [ 36 , 37 ]. There is also a regulatory relationship between circ_0066715 and miR-486 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a co-expression relationship exists between circRNAs and miRNAs. After its transcription, circRNAs cooperate with miRNAs to participate in the regulation of RA [ 36 , 37 ]. There is also a regulatory relationship between circ_0066715 and miR-486 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Histone methyltransferase enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) also plays a role in RA pathogenesis by binding the promoter sites and bringing the H3K27me3 modification to the histone protein which suppresses miR-22-3p synthesis [ 50 ]. Circular RNA-HIPK3 (CircHIPK3) levels in RA patients correlate with the decrease in miR-124a [ 51 ]. In RA, many circular RNAs and miRNAs studied have the potential to be the biomarker of the disease state or the potential therapeutic target [ 72 ].…”
Section: Dysregulation Of Mirna Expression In Human Diseasementioning
confidence: 99%
“…Thus, it can control the differentiation of osteoclasts to affect ovariectomy‐induced bone resorption in mice. The experimental work of Saad el‐din (2022) and the group is the first one to evaluate the role of circHIPK3 RNA/miRNA‐124a in the pathogenesis of the autoimmune‐disorder RA. They concluded that overexpression of circHIPK3 in RA patients significantly enhances the disease severity by stimulating MCP‐1 (Monocyte Chemoattractant Protein‐1) secretion, mainly by acting as a sponge for miRNA‐124a, which is an antagonist of osteoclast differentiation (already discussed in the section 8.3.2.1).…”
Section: Regulation Of Osteoclastogenesismentioning
confidence: 99%